Pengaruh Tenaga Kerja, Nilai Tukar dan Ekspor terhadap Sektor Industri Pengolahan di Indonesia - Toruan, Putri Lumban; Sinaga, Martina Br.; Andiny, Puti; Safuridar, Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Economic growth is the process of increasing a country's production capacity to generate goods and services over a specific period, reflecting the income and well-being of its people. This research aims to analyse the influence of labor, exchange rates, and exports on the Gross Domestic Product (GDP) of the manufacturing sector in Indonesia during the period 2010-2024. The method used is multiple linear regression analysis with the Ordinary Least Square (OLS) approach, using secondary data obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). The research results indicate that all three independent variables, namely labor, exchange rate, and exports, have a positive and significant impact on the GDP of the manufacturing sector, both partially and simultaneously. The coefficient of determination (Adjusted R2) value of 0.9633 indicates that 96.33% of the variation in industrial sector GDP can be explained by these three variables, while 3.76% is influenced by factors outside the model. This research confirms that increased labour productivity, exchange rate stability, and export growth play an important role in strengthening the performance of the manufacturing sector in Indonesia. Therefore, policies focused on improving the quality of human resources, strengthening export competitiveness, and ensuring macroeconomic stability are needed to support the sustainable and globally competitive growth of the manufacturing sector.